O rozważaniach na temat polskich książek dla młodzieży w pierwszych dwóch dekadach XXI wieku. „Między dzieciństwem a dorosłością" Dominika Borowskiego – na marginesie lektury - Nadolna, Marta (Paidia i Literatura, 2023)
In this review, Marta Nadolna considers the positive and negative aspects of Dominik Borowski’s book Między dzieciństwem a dorosłością. O polskich powieściach dla młodzieży w pierwszym dwudziestoleciu XXI wieku [Between Childhood and Adulthood. On Polish Novels for Young Readers in the First Two Decades of the 21st Century], in which Borowski examines how fiction addressed to young readers has changed in the last two decades. Nadolna looks at the advantages and disadvantages of this publication, while citing noteworthy novels for young readerscurrently available on th e publishing market. At the same time, she also examines the themes that this fiction addresses related to civilizational changes and issues of a dysfunctional world, those outlined by Borowski and those ignored by him, also in terms of the amount of concern bestowed on them in the book. Nadolna concludes her review on a positive note, finding Borowski’s book to be reliable as well as amply repaying the reader’s attention.